Different catalytic action of ion-exchanged calcium in steam and CO2 gasification and its effects on the evolution of char structure and reactivity - Yu, Ge; Yu, Dunxi; Liu, Fangqi; Yu, Xin; Han, Jingkun; Wu, Jianqun; Xu, Minghou (Fuel (Guildford), 2019)
•The catalytic action of exchanged calcium in char gasification was investigated.•In H2O gasification the calcium attacked the char by a channeling mode.•In CO2 gasification the calcium attacked the char by a surface recession mode.•The calcium catalytic action significantly affected char structure and reactivity. The catalytic action of ion-exchanged calcium (Ca) in steam and CO2 gasification of coal char was examined. Its effects on pore structure and reactivity of char were also investigated. The char was prepared from a low rank coal that was first demineralized and then loaded with Ca by ion-exchanging. It was gasified at 900 °C in steam or CO2 on a specially designed thermogravimetric reactor (TGR). Partially-gasified chars were extracted at different time intervals and subject to analyses by X-ray diffraction (XRD), nitrogen adsorption measurement and scanning electron microscopy (SEM). The results show that, in steam gasification, the Ca evolves predominantly into CaO particles. They are highly dispersed on the char surface and seen to attack the char by a typical channeling mode. In contrast, the Ca is transformed into both CaO and CaCO3 in CO2 gasification. These Ca-containing compounds undergo significant sintering and form a mixture layer on the char surface. The catalytic action of Ca can be appropriately described by a surface recession mode. These differences are responsible for the evolution of char structure and reactivity. The channeling action of Ca in steam gasification results in a higher surface area and pore volume. The highly dispersed CaO particles more efficiently catalyze the reactions at the early stage of gasification. In CO2, the char possesses a less developed pore structure. The catalysts are in close contact with carbon at the later stage of CO2 gasification and the char remains a higher specific reactivity.